The Inequality of Unwritten Languages: Some Reflections on the Christian Use of the Vernacular in Eastern Africa (Nordic Journal of African Studies, 2004)
Vernacular languages have become theologically important and their translation is a central issue. There is also a need for widespread unwritten vernaculars to be used liturgically. The fact that a language is written as opposed to be only spoken makes for an unequal equality and this is the issue we discuss in this article. The Vatican II resolution allowing the use of vernaculars in the liturgy has to be seen as a vital turning point in the functions of Christianity in many cultures outside the western world. It marks off a stage in an ongoing process of liturgical and theological change.